A Review of Resistance Mechanisms of Synthetic Insecticides and Botanicals, Phytochemicals, and Essential Oils as Alternative Larvicidal Agents Against Mosquitoes - Senthil-Nathan, Sengottayan (Frontiers in Physiology, 2020)
Mosquitoes are a serious threat to the society, acting as vector to several dreadful diseases. Mosquito management programmes profoundly depend on the routine of chemical insecticides that subsequently lead to the expansion of resistance midst the vectors, along with other problems such as environmental pollution, bio magnification and adversely affecting the quality of public and animal health, worldwide. The worldwide risk of insect vector transmitted diseases, with their associated illness and mortality, emphasizes the need for effective mosquitocides. Hence there is an immediate necessity to develop new eco-friendly pesticides. As a result, numerous investigators have worked on the development of eco-friendly-effective mosquitocidal compounds of plant origin. These products have a cumulative advantage of being cost-effective, environmentally benign, biodegradable and safe to non-target organisms. This review aims at describing the current state of research on behavioural, physiological and biochemical effects of plant derived compounds with larvicidal effects on mosquitoes. The mode of physiological and biochemical action of known compounds derived from various plant families as well as the potential of plant secondary metabolites, plant extracts and also the essential oils, as mosquitocidal agents are discussed. This review clearly indicates that the application of vegetal based compounds as mosquito control proxies can serve as alternative biocontrol methods in mosquito management programmes.